Online games training aging brains: limited transfer to cognitive control functions - Van Muijden, Jesse; Band, Guido P.; Hommel, Bernhard (Frontiers in Human Neuroscience, 2012)
The prevalence of age-related cognitive decline will increase due to graying of the global population. The goal of the present study was to test whether playing online cognitive training games can improve cognitive control (CC) in healthy older adults. Fifty-four older adults (age 60-77) played five different cognitive training games online for 30 minutes a day over a period of seven weeks (game group). Another group of 20 older adults (age 61-73) instead answered quiz questions about documentaries online (documentary group). Transfer was assessed by means of a cognitive test battery administered before and after the intervention. The test battery included measures of working memory updating, set shifting, response inhibition, attention and inductive reasoning. Compared with the documentary group, the game group showed larger improvement of inhibition (Stop-Signal task) and inductive reasoning (Raven-SPM), whereas the documentary group showed more improvement in selective attention (UFoV-3). These effects qualify as transfer effects, because response inhibition, inductive reasoning and selective attention were not targeted by the interventions. However, because seven other indicators of CC did not show benefits of game training and some of those that did suffered from potential baseline differences, the study as a whole provides only modest support for the potential of videogame training to improve CC in healthy older adults.